The Effect of Loyalty, Motivation and Work Discipline on Teachers’ Performance: The Case of Public Junior High School in Prabumulih City - Yelli Aswariningsih; Muhammad Idris; Choiriyah Choiriyah (International Journal of Marketing & Human Resource Research, 2026)
This study aims to determine the effect of Loyalty, motivation, and work discipline on the performance of public junior high school teachers in Prabumulih City. To determine the effect of Loyalty on the performance of public junior high school teachers in Prabumulih City, To determine the effect of motivation on the performance of public junior high school teachers in Prabumulih City, To determine the effect of Work Discipline on the performance of public junior high school teachers in Prabumulih City. This type of research is associative-causal quantitative research, which is a study that examines cause-and-effect relationships, where there are independent variables (influencing variables) and dependent variables (influenced variables) (Paramita, 2021: 33). This study was designed to determine the effect of the variables of teacher Loyalty, teacher Motivation, and teacher Discipline on teacher performance variables at public junior high schools in Prabumulih City. The sample in this study consisted of 245 respondents, using cluster random sampling. The data used in this study were primary data, including the number of respondents and the agency profile, and secondary data, using a coequal analysis method. The analysis technique used was multiple linear regression analysis. The results of the study indicate that: (1) Loyalty, motivation, and work discipline have a positive and significant influence on teacher performance at junior high schools (SMP) in Prabumulih City. (2) Loyalty, motivation, and work discipline have a positive and significant influence on teacher performance at junior high schools (SMP) in Prabumulih City. (3) Motivation has a positive and significant influence on teacher performance at junior high schools (SMP) in Prabumulih City. (4) Loyalty, motivation, and work discipline have no positive and significant influence on teacher performance at junior high schools (SMP) in Prabumulih City.